2019
DOI: 10.1111/bjc.12222
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of disengagement from cognitive behavioural therapy for psychosis in a National Health Service setting: A retrospective evaluation

Abstract: Objectives. To evaluate whether demographic and clinical variables are related to disengagement rates in cognitive behavioural therapy (CBT) for psychosis in a clinical setting.Methods. The medical records and symptom severity data (from Health of the Nation Outcome Scales) were analysed retrospectively for 103 referrals for CBT for psychosis in a National Health Service secondary care and Early Intervention in Psychosis team.Results. Overall, 42.7% (n = 44) disengaged from CBT. There was no impact of gender o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Although, in the UK, ethnicity has been shown to be associated with receipt of CBT, with individuals of African and Black-Caribbean ethnicity being less likely to receive CBT for psychosis (Morris et al, 2020). However, our study also highlights that only half of individuals with a FEP attended CBT and this supports findings from a recent UK study which found high disengagement rates (43%) from CBT in the total FEP population (Richardson et al, 2019). Therefore, the barriers to engaging with psychosocial interventions needs to be determined, in order to improve these engagement rates.…”
Section: Discussionsupporting
confidence: 92%
“…Although, in the UK, ethnicity has been shown to be associated with receipt of CBT, with individuals of African and Black-Caribbean ethnicity being less likely to receive CBT for psychosis (Morris et al, 2020). However, our study also highlights that only half of individuals with a FEP attended CBT and this supports findings from a recent UK study which found high disengagement rates (43%) from CBT in the total FEP population (Richardson et al, 2019). Therefore, the barriers to engaging with psychosocial interventions needs to be determined, in order to improve these engagement rates.…”
Section: Discussionsupporting
confidence: 92%
“…There is good evidence that people with psychosis delay accessing treatment (Birchwood et al, 2013) and around a third then disengage from services (Doyle et al, 2014; Kreyenbuhl et al, 2009). Rates of disengagement from CBTp reported in routine clinical practice vary widely (13% [Peters et al, 2015] – 43% [Richardson et al, 2019]), though this is likely to be lower in research settings (e.g. Johns et al, 2019).…”
Section: Factors Likely To Impact the Effectiveness Of Cbtpmentioning
confidence: 99%